Inovasi Teknologi Dalam Pendidikan Klinis Keperawatan Sebagai Strategi Pembelajaran Kreatif: Apa Saja Manfaatnya Bagi Mahasiswa Keperawatan?: Sebuah Literatur Review - hutagaol, rutmauli (Politeknik Kementerian Kesehatan Banjarmasin, 2023)
Nursing education consists of theory and practice. Half of all learning during the educational process is spent in a clinical practice learning environment. However, in practice there are still obstacles that cause the clinical practice process to not be optimal. The application of technological innovation really helps improve performance, performance and quality in all fields, including the world of education. Technology-based learning strategies in the field of education have been proven to increase students' knowledge and skills. This study aimed to identify the types and benefits obtained by students in the use of technological innovation in nursing student clinical practicum. The research method uses a Literature Review study of 10 articles using PRISMA from four online databases: ScienceDirect, ProQuest, Scopus, and Emerald Insight. The keywords used were